Importance of early diagnosis in LMNA‐related muscular dystrophy for cardiac surveillance. Issue 6 (30th September 2019) - Choi, Sun Ah; Cho, Anna; Kim, Soo Yeon; Kim, Woo Joong; Shim, Young Kyu; Lee, Jin Sook; Jang, Se Song; Lim, Byung Chan; Kim, Hunmin; Hwang, Hee; Choi, Ji Eun; Kim, Ki Joong; et al.
Abstract: Introduction: The identification of LMNA ‐related muscular dystrophy is important because it poses life‐threatening cardiac complications. However, diagnosis of LMNA ‐related muscular dystrophy based on clinical features is challenging. Methods: We reviewed the clinical phenotypes of 14 children with LMNA variants, focusing on the cardiac function and genotypes. Results: Most patients presented with motor developmental delay or gait abnormalities. Eight (57%) patients had prominent neck extensor weakness or contractures. All patients showed ankle contractures at an early stage. Regular cardiac surveillance allowed for the detection of dysrhythmias in 57% of patients at a mean age of 14 years (range, 5–26). All patients had missense variants; however, there were no clear phenotype–genotype correlations. Discussion: Early diagnosis of LMNA ‐related muscular dystrophy provides an opportunity for cardiac surveillance, potentially leading to the prevention of cardiac mortality in children.